RANCANG BANGUN ALAT PEMBATAS BAGI JUMLAH PENGUNJUNG BERBASIS ARDUINO VISITOR COUNTER MENGGUNAKAN SENSOR PASSIVE INFRA RED (PIR) DI PLAZA INDIHOME TELKOM AREA SUMEDANG - Dhea Puspita; Ardelia Astriany Rizky (POLITEKNIK PIKSI GANESHA, 2023)
This study aims to design a Limiting Tool for the number of visitors based on Arduino Visitor Counter using Passive Infra Red Sensors. The research method uses literature study and data collection. Data collection techniques are used by making direct observations at Plaza Indihome Telkom, Sumedang Area, and the internet. searching related to the problem. This visitor limiting tool uses Passive Infra Red Sensors at the exit and entrance as a counter to the number of visitors passing through the door. If visitors exceed the specified capacity limit, an information and warning will appear on the LCD screen and the LED lights will turn on so that it can help officers manage the room. This tool is designed to make it easier to calculate the number of visitors entering and leaving the room with a maximum distance of 1 meter from the corner of the coverage area and can only count as a group. Suggestions that need to be considered are using human detection sensors that have a higher sensitivity